Analisis Intensitas Komunikasi Keluarga Jarak Jauh Terhadap Fenomena Culture Shock Mahasiswa Asal Medan Universitas Telkom - Kaur, Sukhwir; Shabrina, Almira (eProceedings of Management, 2023)
Culture shock is a condition that often occurs for overseas students where cultural differences make overseas students experience obstacles in the process of adapting to their new environment. This adaptation process is not easy and can cause confusion because it is difficult to understand and accept values from other cultures due to the presence of a new culture. The intensity of communication between parents and children in dealing with culture shock, especially overseas students from Medan at Telkom University. As is well known, Telkom students include many students who come from outside the island, the author focuses on students from Medan. The method used in this study is a qualitative method using a constructivist paradigm which aims to describe the intimate relationship between humans and the world using a phenomenological approach. In this study, researchers found that the intensity of communicating with family, especially parents, will decrease due to the stages that occur during overseas. Likewise, the role of parents has a very significant impact, as well as words from parents who provide emotional support for their children, will create a positive impact in the child's adaptation process.Keywords-Culture shock, Communication Intensity, Long Distance Family Communication, Regional Students